Plan estratégico para el fortalecimiento de la gestión de la Cooperativa de Ahorro y Crédito Campesino agencia San Pablo de Atenas, cantón San Miguel, provincia Bolívar, período 2023 – 2027 - Almendariz Coloma, Cinthya Elizabeth (2024)
The research shows the development of a strategic plan for strengthening the management of the Cooperativa de Ahorro y Crédito Campesino Agencia San Pablo de Atenas, Cantón San Miguel, Bolívar Province. The type of research used was qualitative due to the purpose of understanding and demonstrating the benefits of field research where the data were taken outside the workplace, that is, the data necessary for the study were obtained in real, uncontrolled conditions. The result has been a rigorous, adaptable and deeply informed strategic plan, capable of merging theory and practice in a precise and harmonious way, ensuring its applicability and effectiveness in the specific context of the cooperative, in line with its particular environment and challenges, taking into account the situational analysis, which has been a key milestone in this process, revealing a detailed and penetrating x-ray of the Cooperative's current situation, which through a holistic diagnosis has become the starting point for strategic decision making, by accurately identifying the critical areas that require attention and the opportunities that can be taken advantage of to strengthen the Cooperative's position in the market. With all the above, it is recommended that the cooperative expand its advertising outreach in various media, such as radio, press, television and billboards, allowing it to identify emerging opportunities and potential threats.